1991
DOI: 10.1161/01.atv.11.3.671
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rejection in rat aortic allografts. An experimental model for transplant arteriosclerosis.

Abstract: Chronic rejection has several histological appearances, depending on the type of organ graft Common to all of them is transplant arteriosclerosis associated with an ongoing inflammatory response in the transplanted graft. To the contrary of classical atherosclerosis, in which the manifestations are mostly focal, proximal, and asymmetric, transplant arteriosclerosis is generalized, and the intimal thickening is concentric In this article, we describe an experimental animal model whereby transplant arteriosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
98
0
5

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(108 citation statements)
references
References 12 publications
5
98
0
5
Order By: Relevance
“…The correlation between adventitial infiltration by inflammatory cells and the ratio of intimal proliferation to medial thickness in untreated allografts demonstrates one of the major features of the model, the importance of inflammation in the injury and response to chronic vascular immune aggression. Nevertheless, Mennander et al 7 reported that adventitial inflammation was predominant during the first month after arterial grafting in this model, a time when medial smooth muscle cells were still present. After this time, the adventitial inflammation decreased in parallel with the disappearance of medial smooth muscle cells.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The correlation between adventitial infiltration by inflammatory cells and the ratio of intimal proliferation to medial thickness in untreated allografts demonstrates one of the major features of the model, the importance of inflammation in the injury and response to chronic vascular immune aggression. Nevertheless, Mennander et al 7 reported that adventitial inflammation was predominant during the first month after arterial grafting in this model, a time when medial smooth muscle cells were still present. After this time, the adventitial inflammation decreased in parallel with the disappearance of medial smooth muscle cells.…”
Section: Discussionmentioning
confidence: 69%
“…The evidence of rejection probably decreases in untreated allografts in relation to the disappearance of smooth muscle cellular antigens 2 months after grafting. 7 In contrast, low doses of cyclosporin could delay the appearance of rejection, so that the inflammation appeared greater in cyclosporin-treated animals than in untreated allografts 2 months after grafting. This inflammation could be related to the persistence of medial cellular antigens, as suggested by the positive correlation between medial smooth muscle cell and adventitial inflammatory cell densities.…”
Section: Discussionmentioning
confidence: 99%
“…Our group first showed (32) that MPA is able to reduce the incidence and severity of GVD in a Brown Norway-to-Lewis transplant model. In addition, MMF reduced the obliteration of renal arteries at a dose of 15 mg/kg/day (33) that no initial immunosuppressive therapy is needed to secure graft function (34,35) and GVD can be investigated independently. In an ACI-to-Lewis model of orthotopic aortic transplantation, intimal proliferation was reduced by 76.1% with the daily treatment of 40-30 mg/kg MMF (8).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently arterial allografts have generally been transplanted without considering the matching of AB0-bloodgroups and of HLA-phenotypes between donors and recipients. Furthermore, only a limited number of studies exist which have investigated the allo-specific immune response induced by arterial allografts, and the majority of them is based on animal models [12][13][14][15][16]. There are only few studies mainly of the 1990s in which the cellular and humoral immune responses as a consequence of venous and especially arterial allo-grafting in humans was investigated [8,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%